2020
DOI: 10.1080/16506073.2020.1790644
|View full text |Cite
|
Sign up to set email alerts
|

The explanatory role of anxiety sensitivity in the association between effortful control and child anxiety and depressive symptoms

Abstract: Introduction:The present study examined the underlying role of anxiety sensitivity in the association between effortful control and anxiety and depressive symptoms in a sample of clinically anxious children. It was hypothesized that effortful control would exert an indirect effect through anxiety sensitivity in relation to child anxiety and depressive symptoms.Method: Clinically anxious children (N = 105; M age = 10.09 years, SD = 1.22; 56.7% female; 61% ethnic minority) and their mothers completed a diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Given the comorbidity of irritability and anxiety (58), impulse control may similarly reduce anxiety levels. Research suggests that greater effort of control is associated with lower anxiety, possibly due to the ability of greater control effort to distract the anxious person from "slowing down" and objectively interpreting internal experiences or suppressing inaccurate thoughts about anxiety-related feelings (59). This evidence suggests that impulse control may be one way to reduce irritability and anxiety symptoms and that interventions of cognitive and behavioral training (CBT) (60) and self-control training (SCT) (61) may be considered for coping with irritability and anxiety in university students.…”
Section: Discussionmentioning
confidence: 99%
“…Given the comorbidity of irritability and anxiety (58), impulse control may similarly reduce anxiety levels. Research suggests that greater effort of control is associated with lower anxiety, possibly due to the ability of greater control effort to distract the anxious person from "slowing down" and objectively interpreting internal experiences or suppressing inaccurate thoughts about anxiety-related feelings (59). This evidence suggests that impulse control may be one way to reduce irritability and anxiety symptoms and that interventions of cognitive and behavioral training (CBT) (60) and self-control training (SCT) (61) may be considered for coping with irritability and anxiety in university students.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that AS, even after controlling the effect of NA, is a significant predictor of developing one of the anxiety disorders (Schmidt, Mitchell, & Richey, 2008 ). Further, the evidence also supported the role of AS in the development of emotional disorders in children (Brown, Meiser-Stedman, Woods, & Lester, 2016 ; Hernandez Rodriguez, 2015 ; Ho, Dai, Mak, & Liu, 2018 ; Knapp, Blumenthal, Mischel, Badour, & Leen-Feldner, 2016 ; Raines et al ., 2020 ; Viana et al ., 2018 ; Wauthia et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%